Oralidade, letramento e identidade - Andrade, Felipe Sousa de [UNESP]; Mendonça, Marina Célia [UNESP] (My University, 2012)
This paper presents partial results of ongoing research of Undergraduate Research held at the Faculdade de Ciências e Letras de Araraquara. The study objective is to reflect on the practice of writing in two Internet sites whose cultural product has features typical of oral tradition, of backlanders. In this article, our proposal is to present a reflection on studies about the relationship between orality, literacy and identity. It is, therefore, a bibliographic study. The results indicate the need to study issues related to speech and writing as part of social practices performed by the subjects, which involve: media materials; forms of movement; ideological values assigned to these uses; identities of subjects.

Este texto apresenta resultados parciais de pesquisa em andamento de Iniciação Científica realizada na Faculdade de Ciências e Letras de Araraquara. O objetivo do estudo é refletir sobre a prática de escrita de internautas em dois sites sertanejos, cujo produto cultural tem características típicas da tradição oral. Neste artigo, nossa proposta é apresentar reflexão sobre estudos que abordam as relações entre oralidade, letramento e identidade. Trata-se, portanto, de um estudo bibliográfico. Os resultados apontam para a necessidade de se abordarem questões relativas à fala e escrita como parte das práticas sociais realizadas pelos sujeitos, as quais envolvem: meios materiais (suportes de textos); formas de circulação; valores ideológicos atribuídos a esses usos; identidades dos sujeitos.
Orality, literacy and identity
Keywords: Orality; Literacy; Identity; Discourse analysis; Estudos bakhtinianos; Gêneros do discurso; Práticas de escrita